Counselling and Education to Improve Adherence Tuberculosis Treatment - Noviati, Elis; Rahayu, Yuyun; Yunitri, Ninik; Herlinah, Lily; Anwar, Syamsul; Baridwan, Syamikar (Indonesian Journal of Global Health Research, 2024)
With the development of nursing science and practice, it is important for nurses to make efforts to control TB, one of the nursing interventions that can be developed in a family-centred TB control programme is counselling and education. This study aims to determine the effectiveness of counselling and education in improving TB treatment adherence in the Puskesmas Ciamis working area. This study is a quantitative study with Quasy experimental design with non-randomised control group design. The population of this study were all TB patients in Puskesmas Ciamis Working Area, a total of 28 patients divided into intervention and control groups. This research was conducted from August 2023 to January 2024. The research instruments used were questionnaires which has been tested for validity and reliability and observation sheets. Data analysis was performed using univariate and bivariate techniques with paired t-test and independent t-test. The results showed that there was an increase in medication adherence before and after the provision of counselling and education in the intervention and control groups. The intervention group experienced a more significant increase in medication adherence p-value 0.027 < 0.05 compared to the control group p-value 0.030 < 0.05, while the comparison of the increase in the intervention and control groups showed a p-value of 0.021 < 0.05. Conclusions: There is a significant effect of the application of counselling and education to improve compliance with the COVID-19 pandemic.